Fundamental Political Trends Affecting the Content of Constitutions: Comparative Study - Sarhang Hamid Barzji; Nawzad Jalal Ebrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Nowadays, the Constitutional Charter is regarded as an important charter in any political system, so that the Constitution determines the way in which governance is exercised and determines the relationship between the authorities and the public rights and freedoms of an individual and the people. Without taking into account the model of the Constitution, no Country in the world is supposed to exist without the Constitution that is why the Constitutional Charter has become one of the most important pillars of any country's political and legal identity. Undoubtedly, there is no constitution drafted outside a particular political ideology. To some extent, every constitution one way or another is the offspring and the product of a certain ideology. Currently, there are different political ideologies for instance (socialism, liberalism, capitalism, totalitarian, fascism, Nazism, etc.). All ideologies and their impacts on the drafting of the Constitution flow from two main sources. These impacts either appear in the form of religion and fundamentalism where their sources are from heavenly books, orders and teachings of God revealed to a Messenger for human being, or the impacts come from such sources where refers to imagination and thought of human i.e., created by human. Many constitutional law experts believe that political ideology whatever it is, reflects on the Constitution. In general, the reflection of political ideologies is tangible in three ways: the constitution either become a secular constitution, or a religious constitution (i.e., opposite of secular), or it becomes a combination of the two (religious and secular). We tried to devote three chapters in this dissertation to analyze this topic. The first chapter is comprised of three discussion sections and each discussion section has three topic sections where a summary on state and the process of constitution evolution and their emergence is discussed. Moreover, light has been shed on some thesis and theories with regard to state and constitution. The second chapter, likewise, has three topic sections, where Secularism evolution and its emergence along with political ideologies that influenced it, especially in the field of constitution, has been researched. The emergence of religious and fundamentalist ideas is also researched in which the influence of religion on constitution is analyzed. In chapter three we discuss the emergence of such types of constitutions that they are neither completely secular nor completely religious, but they are a mixture of secular and religious constitution varieties. Examples from the three constitution types have been discussed and we pointed out in short, the impacts of each constitution type in the society. In the last chapter, we compared the three varieties of constitution with Iraqi constitution 2005. We come into conclusion that there is no constitution without a certain political ideology. Each society is influenced by one of the three constitution categories. Among all three types of constitution, the compound constitution category is more controversial which creates crisis in a country. We come into conclusion that Iraqi constitution is a compound constitution. The articles of Iraqi constitution have secular and religious principles and this has led to its incompatibility in a way that paves the way for political, social and legal crisis. In this regard, we gave a number of examples of 2005 Iraqi constitution.